Baseball [videorecording (DVD)] - Burns, Ken, 1953-; Novick, Lynn; Ward, Geoffrey C. (PBS Home Video ; Distributed by Paramount Home Entertainment, 1994)
It is an epic overflowing with heroes and hopefuls, scoundrels and screwballs. It is a saga spanning the quest for racial justice, the clash of labor and management, the transformation of popular culture, and the unfolding of the national pastime. Here is the story of a nation at work and play. Experience it in ten thrilling "innings" from master storyteller and award-winning filmmaker Ken Burns.